Black phosphorous nanosheets: prospective field emitter - Late, Dattatray J.; Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A. (2015 28th International Vacuum Nanoelectronics Conference (IVNC), 2015)
We report for the first time field electron emission investigations on few layered black phosphorous nanosheets emitter's synthesized using chemical method with thickness similar to 2-5 nm. The turn-on electric field required to draw an emission current density of similar to 10 mu A/cm(2) was found to be similar to 4.2 V/mu m. Furthermore, a few layer black phosphorous nanosheets emitter deliver an large emission current density of similar to 170 mu A/cm(2) at an applied field of similar to 7.5 V/mu m. The emission current versus time plot measured at the preset current values of similar to 5 mu A shows field emission current fluctuations within +/- 10% of the average value indicating the well stable nature of black phosphorous field emitter. Thus, the two dimensional black phosphorous nanosheets synthesized using simple electrochemical exfoliation method can be realized and utilized for the next generation micro/nanoelectronics and flat panel field emission based display applications.

Electrochemically exfoliated black phosphorus nanosheets - prospective field emitters - Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A.; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
Herein we report field emission (FE) investigations on an electrochemically exfoliated few-layered black phosphorus nanosheet emitter at a base pressure of approximately 1x10(-8) mbar. The turn-on electric field required to draw an emission current density of approximately 10 A/cm(2) is found to be about 4.2 V/m. Furthermore, few-layered black phosphorus nanosheet emitters deliver an emission current density of about 170 A/cm(2) at an applied field of about 7.5 V/m. The emission current vs. time plot measured at preset current values of about 5 A shows emission current fluctuations within +/- 10% of the average value, indicating the highly stable nature of the black phosphorus field emitter. Thus, the 2D black phosphorus nanosheets synthesized using the simple electrochemical exfoliation method can be utilized for micro/nanoelectronics and flat panel FE display applications.
Keywords: field emission; Layered compounds; Nanostructures; Phosphorus

Graphene quantum dots as enhanced plant growth regulators: effects on coriander and garlic plants - Chakravarty, Disha; Erande, Manisha B.; Late, Dattatray J. (Journal of the Science of Food and Agriculture, 2015)
BACKGROUNDWe report investigations on the use of graphene quantum dots for growth enhancement in coriander (Coriandrum sativam L.) and garlic (Allium sativum) plants. The as-received seeds of coriander and garlic were treated with 0.2 mg mL(-1) of graphene quantum dots for 3 h before planting. RESULTSGraphene quantum dots enhanced the growth rate in coriander and garlic plants, including leaves, roots, shoots, flowers and fruits, when the seeds were treated with graphene quantum dots. CONCLUSIONOur investigations open up the opportunity to use graphene quantum dots as plant growth regulators that can be used in a variety of other food plants for high yield. (c) 2015 Society of Chemical Industry
Keywords: farming; food; graphene quantum dots; nanotechnology; plant growth regulator

Humidity sensing and photodetection behavior of electrochemically exfoliated atomically thin-layered black phosphorus nanosheets - Erande, Manisha B.; Pawar, Mahendra S.; Late, Dattatray J. (ACS Applied Materials & Interfaces, 2016)
Recent investigations on two-dimensional black phosphorus material mainly highlight work on few atomic layers and multilayers. It is still unknown if the black phosphorus atomically thin sheet is an ideal structure for the enhanced gas solid interactions due to its large surface area. To further investigate this concern, we have synthesized few atomic layer thick nanosheets of black phosphorus using an electrochemical exfoliation method. The surface morphology and thickness of the nanosheet were identified using AFM, TEM, and Raman spectroscopy. The black phosphorus nanosheet thick film device was used for the gas sensing application with exposure to different humidites. Further, the few layer black phosphorus nanosheet based transistor shows good mobility and on/off ratio. The UV light irradiation on the black phosphorus nanosheet shows good response time. The overall results show that the few layer thick film of black phosphorus nanosheets sample exhibits creditable sensitivity and better recovery time to be used in humidity sensor and photodetector applications.
Keywords: black phosphorus; electrochemical exfoliation; humidity sensor; photodetector

SnS2 nanoflakes for efficient humidity and alcohol sensing at room temperature - Bharatula, Lakshmi Deepika; Erande, Manisha B.; Mulla, Imtiaz S.; Rout, Chandra Sekhar; Late, Dattatray J. (RSC Advances, 2016)
We report a one step facile hydrothermal synthesis of layered SnS2 nanoflakes. The as-synthesized nanosheets are characterized using X-ray diffraction, Raman spectroscopy and Transmission Electron Microscopy (TEM). The humidity sensing behavior of SnS2 nanoflake sensor device were investigated in the range of 11-97% of relative humidity (RH) at room temperature. The response time of similar to 85 s and recovery time of similar to 6 s were observed for the SnS2 nanoflake based humidity sensor. A maximum sensitivity of 11.300% is recorded. We also investigate the SnS2 nanoflake based alcohol sensing properties towards methanol, ethanol and iso-propyl alcohol. An exclusive selectivity towards methanol with a response of 1580 is shown as compared to other analytes. The response time of similar to 67 s and recovery time of just 5 s were observed for the SnS2 nanoflake based methanol sensor.

Temperature dependent Raman spectroscopy of electrochemically exfoliated few layer black phosphorus nanosheets - Pawbake, Amit S.; Erande, Manisha B.; Jadkar, Sandesh R.; Late, Dattatray J. (RSC Advances, 2016)
The present investigation deals with temperature dependant Raman spectroscopy of electrochemically exfoliated few layer black phosphorus nanosheets. The temperature dependent study illustrates that softening of the A(g)(1), B-2g and A(g)(2) modes occurs as the temperature increases from 78 K to 573 K. The calculated temperature coefficients for the A(g)(1), B-2g and A(g)(2) modes were found to be -0.028 cm(-1) K-1, -0.028 cm(-1) K-1 and -0.018 cm(-1) K-1 respectively. The observed phenomenon can be utilized for characterizing other emerging two-dimensional inorganic layered materials with atomic thickness.